Assessing Information Technologies for Health. Editorial - Kulikowski, C.; Haux, R. (Yearbook of Medical Informatics, 2006)
To provide an editorial introduction to the 2006 IMIA Yearbook of Medical Informatics with an overview of its contents and contributors.A brief overview of the main theme of “Assessing Information Technology for Health Care”, and an outline of the purposes, readership, contents, new format, and acknowledgment of contributions for the 2006 IMIA Yearbook.Assessing information technology (IT) in biomedicine and health care is emphasized in a number of survey and review articles. Synopses of a selection of best papers for the past 12 months are included, as are original papers on the history of medical informatics by pioneers in the field, and selected research and education programs. Information about IMIA and its constituent societies is given, as well as the authors, reviewers, and advisors to the Yearbook.The 2006 IMIA Yearbook of Medical Informatics highlights as its theme one of the most significant yet difficult aspects of information technology in health: the assessment of IT as part of the complex enterprise of biomedical research and practice. It is being published in a new format with a wide range of original survey and review articles.
Keywords: Editorial; 2006 IMIA Yearbook of Medical Informatics; IT Assessment for Health; Surveys of Biomedical Informatics; Reviews of Biomedical Informatics; History of Biomedical Informatics; IMIA and its societies